The use of prealbumin concentration as a biomarker of nutritional status in treated phenylketonuric patients - Rocha, J.C. (2010)
BACKGROUND/AIMS: The neurological sequelae resulting from untreated phenylketonuria are diminished by the success of early introduced and continued dietary treatment. Nowadays, nutritional status is gaining importance in the follow-up of these patients. The aim of this work was to study the relevance of prealbumin concentration as biomarker of protein nutritional status of phenylketonuric patients.METHODS: We collected data from 69 phenylketonuric patients on food intake, blood prealbumin and blood phenylalanine concentrations. Protein insufficiency was defined as prealbumin z-scores below the 5th percentile of reference population. Additionally, we considered a prealbumin concentration of 20 mg/dl as a threshold level.RESULTS: Nine patients (13%) showed signs of protein insufficiency. When the threshold of 20 mg/dl for prealbumin was used, we found 38 patients (55%) with low prealbumin concentrations.CONCLUSION: A significant group presented signs of protein insufficiency either using prealbumin z-scores or prealbumin concentration threshold, especially in milder forms of the disease. The results of this seem to confirm the already described threshold level for prealbumin concentration, suggesting that its measurement may be important for nutritional status evaluation, preventing protein insufficiency in milder forms of phenylketonuria.